2005
DOI: 10.1039/b413285h
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of nitropyridines by nitration of pyridines with nitric acid

Abstract: Nitration of pyridines 1a-o with nitric acid in trifluoroacetic anhydride, gave the corresponding 3-nitropyridines 6a-n in yields of 10-83%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Preparation of 2 based on Katrizky methods as follows [10]. Trifluoroacetic anhydride (10 ml, 42 mmol) was chilled in an ice bath and, 17 mmol of pyridines (1) were slowly added and stirred at chilled conditions for 2 h followed by the dropwise addition of concentrated nitric acid (1.9 ml, 36 mmol).…”
Section: Procedures Reaction Synthesis Of 3-nitropyridines (2)mentioning
confidence: 99%
“…Preparation of 2 based on Katrizky methods as follows [10]. Trifluoroacetic anhydride (10 ml, 42 mmol) was chilled in an ice bath and, 17 mmol of pyridines (1) were slowly added and stirred at chilled conditions for 2 h followed by the dropwise addition of concentrated nitric acid (1.9 ml, 36 mmol).…”
Section: Procedures Reaction Synthesis Of 3-nitropyridines (2)mentioning
confidence: 99%
“…It has been suggested that the reaction mechanism implies a [1,5] sigmatropic shift of the nitro group. Recently, Katrizky and coworkers [157] have developed an improved method that consists of the in situ generation of dinitrogen pentoxide from nitric acid and trifluoroacetic anhydride (TFAA) (Scheme 16.50).…”
Section: Electrophilic Substitution Reactionsmentioning
confidence: 99%
“…Dibutyl (2E,2¢E)-3,3¢-(Thiophene-3,4-diyl)diacrylate (69,R 1 =CO 2 Bu); Typical Procedure: [144] The reaction of 3,4-dibromothiophene (68; 0.242 g, 1.00 mmol), butyl acrylate (0.512 g, 4.00 mmol), and K 2 CO 3 (4.00 mmol) at 130 Palladium-containing nanostructured silica 71 bearing trialkyl(4-pyridyl)ammonium binding sites can be used as a heterogeneous catalyst for Heck coupling reactions. This methodology is especially useful because of the easy recovery and reuse of the catalyst.…”
Section: S Brmentioning
confidence: 99%
“…[89][90][91][92][93][94][95][96][97]257] New strategies that have been published include diastereoselective Friedel-Crafts alkylation reactions, e.g. [129] A new method, already successfully applied to the nitration of pyridines and pyridine analogues, [130] has been tested for the direct nitration of thiophenes. [100] Scheme 19 Diastereoselective Friedel-Crafts Alkylation Reactions [98] MeO OH X 2-[1-(4-Methoxyphenyl)-2-nitropropyl]-5-methylthiophene (44,X=NO 2 ); Typical Procedure: [98] 1-(4-Methoxyphenyl)-2-nitropropan-1-ol (106 mg, 0.500 mmol) was placed in a flame-dried flask, dissolved in anhyd CH 2 Cl 2 (10 mL), and cooled to -78 8 8C.…”
mentioning
confidence: 99%